Effect of high nitrate vegetable juice supplementation on plasma nitrate and blood pressure in adults: a pilot randomized crossover intervention in healthy volunteers. (6th June 2022) - Elsahoryi, Nour A.; Cardwell, Christopher; Gilchrist, Sarah; Woodside, Jayne V.
Abstract: Abstract : Beetroot juice (BRJ) has been demonstrated to decrease blood pressure (BP) due to the high inorganic nitrate content. This pilot randomized crossover trial aimed to investigate the effect of two different high nitrate vegetable juices on plasma nitrate concentrations and BP in healthy adults. Eighteen healthy volunteers were randomized to receive 115 ml of BRJ or 250 ml of green leafy vegetable juice for 7 d which contained similar amounts of nitrate (340 mg) daily. Blood samples were collected, and clinic BP measured at baseline and at the end of each juice consumption. Daily home BP assessment was conducted 2 h after juice consumption. Nitrate and nitrite concentrations were analysed using a commercially available kit on a Triturus automated ELISA analyser. Hills and Armitage analysis was used for the two-period crossover design and paired sample t -tests were performed to compare within-group changes. Plasma nitrate and nitrite concentrations significantly increased and there was a significant reduction in clinic and home systolic blood pressure (SBP) mean during the BRJ period ( P -values 0⋅004 and 0⋅002, respectively). Home diastolic blood pressure (DBP) reduced significantly during green leafy vegetable juice consumption week ( P -value 0⋅03). The difference between groups did not reach statistical significance during the formal crossover analysis adjusted for period effects. BRJ and green leafy vegetable juice may reduce SBP or DBP, but there was no statistically significant difference between the two juices, although this was only a pilot study.